S3 Guideline for the treatment of psoriasis vulgaris, update – Short version part 1 – Systemic treatment. (11th May 2018) - Nast, Alexander; Amelunxen, Lasse; Augustin, Matthias; Boehncke, Wolf‐Henning; Dressler, Corinna; Gaskins, Matthew; Härle, Peter; Hoffstadt, Bernd; Klaus, Joachim; Koza, Joachim; Mrowietz, Ulrich; Ockenfels, Hans‐Michael; et al.
Summary: The German guideline for the treatment of psoriasis vulgaris was updated using GRADE methodology. The guideline is based on a systematic literature review completed on December 1, 2016, and on a formal consensus and approval process. The first section of this short version of the guideline covers systemic treatment options considered relevant by the expert panel and approved in Germany at the time of the consensus conference (acitretin, adalimumab, apremilast, cyclosporine, etanercept, fumaric acid esters, infliximab, methotrexate, secukinumab and ustekinumab). Detailed information is provided on the management and monitoring of the included treatment options.